Under Occupation : Resistance and Struggle in a Militarised Asia-Pacific. - Broudy, Daniel (Cambridge Scholars Publishing, 2013)
This edited volume provides a vehicle for the expression of geographical and historical perspectives on the militarisation of East Asia and the Pacific. Among the questions the authors explore are: How have groups and individuals variously enforced, justified, supported, resisted, and acquiesced in military occupation? How have concepts of nationality, identity, and self-determination been shaped, reshaped, and erased by historical processes? How can communities escape from their perceived or ...